Accuracy of Liver-Type Fatty Acid-Binding Protein in Predicting Acute Kidney Injury: A Meta-Analysis. (9th September 2021) - Chiang, Ting-Hui; Yo, Chia-Hung; Lee, Gin Hoong; Mathew, Amy; Sugaya, Takeshi; Li, Wen-Yi; Lee, Chien-Chang
Abstract: Background: Liver-type fatty acid–binding protein (L-FABP) is a promising biomarker for the early prediction of acute kidney injury (AKI). However, the clinical utility of L-FABP in different populations or settings remains unclear. We present a meta-analysis of studies evaluating the performance of L-FABP in AKI prediction. Methods: We performed a literature search in MEDLINE, EMBASE, and Cochrane library, using search terms "acute kidney injury" and "L-FABP." Studies investigating the performance characteristics of L-FABP for the early diagnosis of AKI were included. Data about patient characteristics, diagnostic criteria of AKI, quantitative data required for construction of a 2 × 2 table (number of participants, sensitivity, specificity, and case number), study settings, and outcomes were extracted. The bivariable model was applied to calculate the estimated sensitivity and specificity of L-FABP. A summary ROC curve was created by plotting the true‐positive rate against the false‐positive rate at various cutoff values from different studies. Results: We found 27 studies reporting measurement of urine (n = 25 studies) or plasma (n = 2 studies) L-FABP. Overall, the estimated sensitivity was 0.74 (95% CI: 0.69–0.80) and specificity was 0.78 (95% CI: 0.71–0.83). L-FABP demonstrated a stable area under the ROC of 0.82 (95% CI: 0.79–0.85) in variable clinical settings including intensive care unit, surgery, and contrast-induced AKI. In subgroup analysis excluding pediatric and post radiocontrast exposure cohorts, L-FABP had comparative diagnostic performance with neutrophil gelatinase associated lipocalin (NGAL). Conclusions: Despite broad prevalence, L-FABP is a clinically useful marker with moderate accuracy in variable clinical settings as demonstrated in our subgroup analysis. Except for pediatric patients and those post-radiocontrast exposure, L-FABP has comparable discriminative capability as NGAL.